2002
DOI: 10.1002/jnr.10444
|View full text |Cite
|
Sign up to set email alerts
|

Golden mean to longevity: Rareness of mitochondrial cytochrome b variants in centenarians but not in patients with Parkinson's disease

Abstract: To test the hypothesis that centenarians are free from deleterious mitochondrial variations, we analyzed amino acid variations in the cytochrome b molecule of 64 Japanese centenarians. Although the frequencies of some variations, such as N260D and G251S, differed significantly between centenarians and patients with Parkinson's disease, the most striking feature of centenarian cytochrome b was the rareness of amino acid variations in contrast to the variety of amino acid replacements in patients with Parkinson'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 12 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…We previously reported the absence of certain mtDNA variants in centenarians and their presence in patients with Parkinson's disease. 34 These findings imply that these variants are not beneficial for long-term survival but appear to predispose individuals to certain adult-onset diseases, and that centenarians are genetically hitting the golden mean. In the present study, the association between subhaplogroup D4e and elite EMA status could be explained by improved mitochondrial function through the absence of non-synonymous variants in subhaplogroup D4e.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the absence of certain mtDNA variants in centenarians and their presence in patients with Parkinson's disease. 34 These findings imply that these variants are not beneficial for long-term survival but appear to predispose individuals to certain adult-onset diseases, and that centenarians are genetically hitting the golden mean. In the present study, the association between subhaplogroup D4e and elite EMA status could be explained by improved mitochondrial function through the absence of non-synonymous variants in subhaplogroup D4e.…”
Section: Discussionmentioning
confidence: 99%
“…We detected a novel mtDNA nucleotide variation: polymorphism of mtDNA 15497 guanine/adenine (Mt15497G→A). Although Mt15497G→A leads to the Gly251Ser amino acid replacement on human cytochrome b, it is unknown whether a functional alteration of the mitochondrion is induced by the Gly251Ser replacement (Tanaka et al 2002). Therefore, to elucidate an association between the Mt15497G→A polymorphism and obesity, we examined a relatively large sample size of middle-aged to elderly Japanese individuals comparing body size, body composition, and regional body fat distribution of subjects carrying the G or A alleles of Mt15497.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mtDNA mutations impacting mitochondrial function and ATP production link with abnormal insulin release and b-cell development, insulin resistance, and diabetes (Poulton et al, 1998;Silva et al, 2000;Kaufman et al, 2015). In this context, Tanaka et al (2002) demonstrated that single nucleotide polymorphisms in mtDNA (mtSNPs) may result in decreased energy expenditure, leading to obesity. Moreover, several studies have associated mtSNPs with type II diabetes and obesity (Rivera et al, 1999;Fuku et al, 2002;Okura et al, 2003;Guo et al, 2005).…”
Section: Transmission Of Metabolic Diseases Linked To Mitochondria Dymentioning
confidence: 99%